Building Scalable Data Processing Systems with Kafka on Kubernetes - Sudheer Vankayala, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Real-time data processing has become a critical requirement for modern enterprises, presenting unique challenges in scalability, reliability, and performance. This technical article explores the synergy between Apache Kafka and Kubernetes in building robust, production-grade streaming architectures. This article presents a detailed examination of how Kafka's distributed streaming capabilities, combined with Kubernetes' container orchestration, create a resilient foundation for handling high-velocity data streams. Through practical examples from insurance claims processing and manufacturing IoT systems, we demonstrate proven patterns for deployment, scaling, and monitoring. The article provides deep technical insights into topic partitioning strategies, StatefulSet configurations, and operational best practices while addressing critical concerns around security, cost optimization, and disaster recovery. This article shows that this architectural approach can significantly reduce processing latency, handle unpredictable workload spikes, and maintain system reliability at scale, making it particularly valuable for enterprises dealing with real-time analytics and event-driven applications.
Keywords: Event Streaming Architecture; Container Orchestration; Real-Time Data Processing; Distributed Systems; Cloud-Native Infrastructure